2020
DOI: 10.1002/mnfr.201900599
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid and Alpha Linolenic Acid Improve Cholesterol Homeostasis in Obesity by Modulating Distinct Hepatic Protein Pathways

Abstract: Scope: High-fat diet (HFD)-induced obesity impairs macrophage-to-feces reverse cholesterol transport (RCT). It is hypothesized that dietary supplementation with the polyunsaturated fatty acids conjugated linoleic acid (CLA) or alpha linolenic acid (ALA) would prevent HFD-impaired RCT by modulating hepatic protein pathways. Methods and results: ApoE3L.CETP mice are fed a HFD supplemented ± CLA or ALA for 12 weeks and in vivo macrophage-to-feces RCT is determined. Hepatic cholesterol transporters and the hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…For in vivo studies, the CLA used was a commercially available mixture of equal amounts of c9t11 and t10c12 (1:1; den Hartigh, 2019; Koba & Yanagita, 2014). Indeed, most in vivo studies have used mixtures of CLA for dietary lipid supplementation (O'Reilly et al, 2020; Tsuboyama‐Kasaoka et al, 2000; Y. Wang & Jones, 2004) because it is more closely related to the application in human health. For in vitro mechanistic studies, purified CLA was mixed with 100% ethanol, dried in a nitrogen atmosphere, and then dissolved in 0.1 M NaOH for a fatty acid‐NaOH stock solution of 100 mM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For in vivo studies, the CLA used was a commercially available mixture of equal amounts of c9t11 and t10c12 (1:1; den Hartigh, 2019; Koba & Yanagita, 2014). Indeed, most in vivo studies have used mixtures of CLA for dietary lipid supplementation (O'Reilly et al, 2020; Tsuboyama‐Kasaoka et al, 2000; Y. Wang & Jones, 2004) because it is more closely related to the application in human health. For in vitro mechanistic studies, purified CLA was mixed with 100% ethanol, dried in a nitrogen atmosphere, and then dissolved in 0.1 M NaOH for a fatty acid‐NaOH stock solution of 100 mM.…”
Section: Methodsmentioning
confidence: 99%
“…For in vivo studies, the CLA used was a commercially available mixture of equal amounts of c9t11 and t10c12 (1:1; den Hartigh, 2019; Koba & Yanagita, 2014). Indeed, most in vivo studies have used mixtures of CLA for dietary lipid supplementation (O'Reilly et al, 2020;Tsuboyama-Kasaoka et al, 2000;Y. Wang & Jones, 2004) because it is more closely related to the application in human health.…”
Section: The Cla Preparationmentioning
confidence: 99%
“…In contrast with the critical role of cholesterol on the entire RCT pathway [ 28 ], the effect of PUFA supplementation on m-RCT did not differ from that observed when saturated fatty acids were added to the high-fat, high-cholesterol diet [ 180 ]. Although this lack of effect contrasts with the stimulating effects of ω-3 PUFA C20:5 EPA and C22:6 DHA on the rate of fecal macrophage-derived cholesterol excretion [ 30 , 161 ], these results would be consistent with the absence of effects when comparing low- and high-soybean oil-enriched diets (which are rich in n-6 PUFA) in mice [ 30 ] or when evaluating the impact of alpha linoleic acid supplementation (representing 0.7% of calories from fats) in a high-fat diet in CETP-expressing apoE3 Leiden mice [ 165 ]. Importantly, this PUFA did not induce a further increase in the expression of ABCG5 and G8 in mice [ 30 , 180 ], rather suggesting differences in the bioactivity of PUFA species among different supplemented diets.…”
Section: Effects Of Pufa On Rct In Animal Modelsmentioning
confidence: 64%
“…The impact of rumenic acid on m-RCT is more controversial. In the study mentioned above on humanized apoE3Leiden-CETP-expressing mice fed with a high-fat diet supplemented with CLA (representing 0.7% of calories from fats), cholesterol mobilization from macrophages to the plasma, liver, and feces was not improved compared with control animals [ 165 ]. Conversely, the presence of 4% w/w of total fatty acids of rumenic acid in milk administered to hamsters caused an increase in HDL levels and the upregulation of ABCA1 expression [ 166 ].…”
Section: Effects Of Tfa On Rct In Animal Modelsmentioning
confidence: 99%
“…The most predominant biologically active isomers in natural CLA are "c9, t11" CLA, and "t10, c12" CLA (Giordano et al, 2011). Previous studies have shown that natural CLA has the potential to reduce body fat (Sandri et al, 2020) and cholesterol (O'Reilly et al, 2020;Yeonhwa Park et al, 2010), and enhances immunity (Park et al, 2008). In addition to being the essential fatty acid for human, CLA is also the material for synthesizing some structured lipids (Zou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%